Socioeconomic Influence on Political Choices in Elections in Temanggung Regency - Sistyawan, Dwanda Julisa; Gisymar, Najib A; Sarkanto, Sarkanto; Fristianti, Nadya Dhea (Politicon : Jurnal Ilmu Politik, 2025)
This study aims to analyze the influence of socio-economic factors on political participation in elections in Temanggung Regency. The research method employed is a quantitative combination of a survey involving 600 respondents from various districts in Temanggung Regency. The results reveal that factors such as education level, type of employment, and economic sector significantly impact community political participation. Higher education levels tend to enhance political awareness and engagement. Meanwhile, the type of employment and economic sectors influence patterns of political involvement. Economic issues such as unemployment and poverty present significant challenges faced by the people of Temanggung ahead of the elections. The recommendations of this study include increasing access to education, economic empowerment, and inclusive policies to encourage broader and more representative political participation.